Tectonic and climate controls on river terrace formation on the northeastern Tibetan Plateau: Evidence from a terrace record of the Huangshui River. (20th May 2023) - Ma, Zhenhua; Peng, Tingjiang; Feng, Zhantao; Li, Xiaomiao; Song, Chunhui; Wang, Qi; Tian, Wanxin; Zhao, Xiaoyan
Abstract: River terraces are significant geomorphic markers of climate and tectonics. However, the competing roles of bedrock uplift and climatic change in the formation of fluvial terraces remain uncertain. A series of well-developed terrace sequences of the Yellow River and its tributaries formed in intermontane basins and on mountains on the NE Tibetan Plateau. A flight of 10 river terraces has been preserved along the lower Huangshui River, a major tributary of the Yellow River. Based on electron spin resonance (ESR) analyses we found that the oldest river terrace of the lower Huangshui River on Alagu Mountain formed at ∼1.2 Ma. Moreover, the results of provenance analysis based on detrital zircon U–Pb dating showed that the fluvial system of the modern Huangshui River was established before ∼1.2 Ma. After comparing the ages of the oldest river terraces of major rivers on the NE Tibetan Plateau, we found that they are essentially synchronous. Then, we comprehensively analyzed the climate and tectonic conditions, and suggested that the abrupt climate change dominated the synchronous formation of the oldest terraces of major rivers at approximately 1.2 Ma on the NE Tibetan Plateau. Moreover, to assess the effects of the rock uplift rate on river terrace formation, we integrated 22 terrace sequences with long timescales on the NE Tibetan Plateau, and we found that the preservation rate of river terraces is linearly correlated with the rock uplift rate. Thus, our results suggest that the timing of terrace formation is controlled by abrupt climate change and that the amount of terrace formation/preservation is controlled by the rock uplift rate on the NE Tibetan Plateau.